Mode stresses for the interaction between an inclined crack and curved crack in plane elasticity - Nik Long, Nik Mohd Asri; Aridi, Mohd Radzi; Eshkuvatov, Zainidin K. (Hindawi Publishing Corporation, 2014)
The interaction between the inclined and curved cracks is studied. Using the complex variable function method, the formulation in hypersingular integral equations is obtained. The curved length coordinate method and suitable quadrature rule are used to solve the integral equations numerically for the unknown function, which are later used to evaluate the stress intensity factor. There are four cases of the mode stresses; Mode I, Mode II, Mode III, and Mix Mode are presented as the numerical examples.